Investigation Into Local Additives as Substitute To Standard Viscosifier; Advances in Drilling Technology - Boyi, George; Amadi, Godswill (Journal of Earth Energy Engineering, 2023)
In Nigeria, drilling companies import a bulk of drilling fluid materials that they use to carry out their respective operations. This has been a major concern to oil and gas industries since these drilling fluid materials cannot be recycled, are highly expensive in terms of foreign exchange, are not environmentally friendly, not very effective, and non-biodegradable. This work presents an experimental investigation into the reliability of the use of local materials as a substitute to conventional viscosifiers. Local materials used in the analysis are mucuna solannie (Ukpo), brachystegia eurycoma (Achi), and detarium microcarpium (Ofo). The results obtained from the experimental analysis show that they compared closely to the standard viscosifer formulated with Pac-R. The results showed that the density, specific gravity, pH, yield stress, gel strength, plastic viscosity, and yield point of mud formulated from local materials compared favourably with that of the imported viscosifiers. An increase in concentration of the local sample also favoured its potential to replace the Pac-R. In terms of cost, cutting carrying ability, and positive environmental impacts, the local materials could serve the Nigerian drilling company better.